(untitled) (The Research of Medical Science Review, 2025)
Objective: Evaluation of mean pain and mean mouth opening before and after intraarticular injection of platelet-rich plasma in patients presenting with temporomandibular joint dysfunction. Introduction: Temporomandibular joint dysfunction syndrome (TMDs) is found in 40–60% of the community. It is more common in female population, and primarily affect people in 20-40 years of age. Methodology: A quasi-experimental study was conducted at PIMS Islamabad from June 2023 to July 2024 using consecutive sampling. Patients with temporomandibular joint dysfunction having age range in between 18 to 60 years were included. Pregnancy, history of recent steroid injections, infections, significant joint injury and previous surgeries were among the exclusion criteria. PRP was equipped using double spin technique followed by injection on affected joint area. Pain and mouth opening was documented at preintervention, 30mints after single injection of PRP, 1st, 2nd and 6th week on follow up. Results: The study of 50 participants (68% female) presented a marked decline in pain, with VAS scores reducing from 6.42±1.46 pre-intervention to 1.02±0.38 by week six, and mouth opening improving from 19.66±3.65 mm to 35.58±2.52 mm. These changes were statistically significant (p = 0.000), reflecting substantial pain respite and functional regaining over the six-week period. Conclusion: Significant improvement in mouth opening and decrease in VAS discomfort levels over a six-week period demonstrated the high efficacy of intra articular platelet-rich plasma (PRP) injection in temporomandibular joint dysfunction syndrome patients.